Axolotl - a supermodel for tissue regeneration - Goršič, Maša (Slovenian veterinary research, 2007)
The process of regeneration -the regrowth of tissue or body part, have been focus of human attention for many centuries. Among vertebrates, the ability toregenerate lost tissue or organs is best. developed in urodele amphibians, such as axolotl (Ambystoma mexicanum), which can replace lost tissue throughout adulthood. Axolotl is neotenic amphibian that can regenerate wide range of organs including limbs, tails, gills, heart, spinal cord, jaws. Amongthe organs they can regenerate, the limb has been most widely studied so that it provides the basis of knowledge about the mechanisms regulating tissueregeneration. Limb regeneration progresses through a series of steps: wound healing, dedifferentiation and re-differentiation. A number of genes involved in the activation of regeneration have been already identified and cloned, but to this moment, exact molecular mechanisms of regeneration processare not yet known. With the new techniques of functional genomics that will help us to identify candidate genes and testing their functions, there are good prospects to discover the whole mystery of regeneration and achieve the ultimate goal - regeneration in mammals.
Keywords: aksolotl; Celična diferenciacija; Cell Differentiation; Ekstremitete; Extremities; Gene Expression Regulation; genetika; Gensko izražanje, regulacija; Rana, celjenje; Regeneracija; Regeneration; tkiva; Urodela; Wound Healing